Оцінка перспектив застосування S-вмісних птеридинів при токсичних ураженнях печінки - Логвіненко, Н.; Коваленко, С.; Швець, Володимир Миколайович; Logvinenko, N.; Kovalenko, S.; Shvets, V. M. (My University, 2024)
S-containing pteridines reduce the severity of hepatotoxic effects caused by tetrachloromethane administration. The hepatoprotective effect of the obtained compounds is based on their ability to increase the level of GSH, inhibit lipid peroxidation and reduce the level of pro-oxidant compounds. The identified, most active compound is a promising hepatoprotective and metabolitotropic agent and is subject to further in-depth biochemical and histochemical studies.
Assessment of the prospects for the use of S-containing pteridins in toxic liver damage